PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN PEGAWAI PUSKESMAS DI PADURENAN - Putri Lestari; Edison Siregar (Fakultas Ekonomi Universitas Kristen Indonesia, 2023)
This researched aim to identify and analyze effects of work motivation and discipline on qualities of services for Puskesmas employees in Padurenan. The data source using was primary data which was obtain by distributing questionnaire to 32 people using purposive sampling, and populations in these studies were non-medical employee at Padurenan Public Health Center with a total of 32 respondents. Take as many samples as specified in the population. The independents variable in these studies consist of work motivation and disciplines, while dependent variables is service quality. The analysis used in these studies includes validity tested, reliability tested, classic assumption tested, t tested, F tested, multiple linear regressions analyst, and the coefficients of determination (R2). While secondaries data was obtained through library researched by read book and others data source that are still relate to these researched. Base on results of t-tested researched conduct from result of regression analyst, variable of motivations and work disciplines have a positives and significant effects on qualities of service for Puskesmas employees in Padurenan. The coefficients of determination tested show an R-square values of 86.8%, which mean that the variable service qualities is influence by the independents variable, namely motivations and work disciplines, while remaining 13.2/% is influence by others variable not examine in these studies. Keywords: motivation, work discipline, service quality.